2019
DOI: 10.5021/ad.2019.31.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Synthesized Ceramide Induces Growth of Dermal Papilla Cells with Potential Contribution to Hair Growth

Abstract: Background: The ceramide is known to play an important role in the formation of intracellular lipids, and play a crucial role as a barrier for skin and hair cuticle. Recent study has revealed that ceramide has potential effect on hair growth in a mouse model. However, the role of ceramide in human dermal papilla cells (hDPCs) known to play an important role in hair growth is not well understood yet. Objective: The goal of this study was to investigate the effect of synthetic ceramides (oleyl and stearyl cerami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Specifically, we found that the levels of DAG and ceramide at the plasma membrane decreased after activation of Wnt/β‐catenin signaling with Wnt3a treatment (Table S1 ). Both DAG and ceramide have been associated with Wnt signaling in developmental, homeostatic, and tumorigenic processes [ 19 , 45 , 46 , 47 ]. The binding of the canonical Wnt ligand to the Fz receptor at the plasma membrane causes endocytic internalization of the Wnt‐receptor complex and co‐internalization of the membrane lipids that are found in the vicinity of the Wnt‐receptor complex [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we found that the levels of DAG and ceramide at the plasma membrane decreased after activation of Wnt/β‐catenin signaling with Wnt3a treatment (Table S1 ). Both DAG and ceramide have been associated with Wnt signaling in developmental, homeostatic, and tumorigenic processes [ 19 , 45 , 46 , 47 ]. The binding of the canonical Wnt ligand to the Fz receptor at the plasma membrane causes endocytic internalization of the Wnt‐receptor complex and co‐internalization of the membrane lipids that are found in the vicinity of the Wnt‐receptor complex [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cer is an essential component of the physical barrier of skin. It has been reported that synthetic Cer may induce the proliferation of human dermal papilla cells by regulating the Wnt/β-catenin and BMP2/4 signaling pathways, thereby stimulating hair growth [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the IHC results showed that CGE topical treatment increased β-catenin expression in HF tissue compared to the Veh group. Previous studies elaborated on the crosstalk between β-catenin and Akt/ERK1/2 pathways, and their involvement in hair growth promotion [ 42 44 ], and β-catenin expression is promoted by pGSK3β-pAKT-pERK signaling in hDPCs [ 45 ]. A previous study reported that β-catenin regulates SHH expression, and the deletion of β-catenin inhibited SHH expression and inhibited anagen induction [ 39 ].…”
Section: Discussionmentioning
confidence: 99%